An update on current pharmacotherapy options for dyspepsia. (September 2013) - Moshiree, Baharak; Barboza, Jose; Talley, Nicholas
<x xml:space="preserve">Abstract</x> Introduction: Functional dyspepsia (FD) is a highly prevalent and challenging disorder which impacts patients' quality of life and poses a considerable socioeconomic burden. Given the vagueness of the definition of FD based on the current Rome III criteria's expert opinion, the diagnosis of FD continues to be one of exclusion. Despite efforts to better define what constitutes FD, validity of such diagnostic criteria remains controversial given the lack of a distinct pathophysiologic mechanism. Areas covered: New insights into the pathophysiology of FD have expanded our treatment options for the syndrome. This review will discuss the current pharmacologic treatments of FD with particular focus on the more robust randomized controlled trials to date. Expert opinion: Recently, the understanding of the pathophysiology of FD has evolved with novel hypothesis such as sensorimotor abnormalities of the stomach or duodenum, genetic polypmorphisms, psychological comorbidities, food sensitivities and allergies, and immune dysregulation found to be possibly responsible for its pathogenesis. Despite the expanding knowledge about the likely multifactorial pathophysiology of FD, its treatment remains a challenge.